Lithium niobate single crystal, method for producing lithium niobate single crystal, and AR glass

By controlling platinum concentration and using a platinum-iridium alloy crucible, the method produces lithium niobate single crystals with reduced light absorption, addressing image quality issues in AR glass.

JP7626164B2Active Publication Date: 2025-02-04SUMITOMO METAL MINING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023090005
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-02-04
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

Existing lithium niobate single crystals used in AR glass exhibit significant light absorption in the visible light area, affecting image quality by causing color shifts when images are displayed.

Method used

The production method involves controlling the platinum concentration in the single crystal to 1.0 ppm or less and using a platinum-iridium alloy crucible to minimize platinum elution, ensuring low light absorption coefficients at wavelengths of 470 nm and 600 nm.

Benefits of technology

The resulting single crystals exhibit reduced light absorption in the visible light area, maintaining image integrity and color accuracy in AR glass applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626164000008
    Figure 0007626164000008
  • Figure 0007626164000009
    Figure 0007626164000009
  • Figure 0007626164000001
    Figure 0007626164000001
Patent Text Reader

Abstract

To provide a lithium niobate single crystal that has less absorption of light with a wavelength in a visible light region.SOLUTION: A lithium niobate single crystal has platinum concentration of 1.0 ppm or less in the single crystal.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium niobate single crystal, a method for producing the lithium niobate single crystal, and AR glass. [Background technology]

[0002] The qualities required for the waveguide materials used in AR glasses (augmented reality glasses) are (1) high refractive index, (2) low light absorption in the visible light range, (3) high flatness when processed into wafer form, and (4) low specific gravity.

[0003] Because the material for the waveguide in AR glasses has a high refractive index, the field of view (FOV) of the images displayed on the AR glasses can be made wider, enabling more immersive and realistic images to be displayed. High refractive index glass has generally been used as the material for the waveguide in AR glasses up until now, but the refractive index of high refractive index glass is thought to be limited to around 2.1, and the use of lithium niobate single crystals, which has a refractive index of 2.2, higher than that of glass, is being investigated.

[0004] Lithium niobate (LiNbO3; sometimes abbreviated as LN) single crystal is an artificial ferroelectric crystal with a melting point of approximately 1250°C and a Curie temperature of approximately 1140°C. LN single crystal substrates obtained by cutting and polishing LN single crystals are mainly used as a material for surface acoustic wave elements (SAW filters) installed in mobile communication devices.

[0005] If the waveguide for AR glasses absorbs light at wavelengths in the visible light range, the light will be attenuated significantly when the image passes through the waveguide via total reflection, resulting in the color of the image displayed on the AR glasses differing from the intended image.

[0006] Patent Document 1 discloses a method for producing lithium niobate single crystals for use in optical elements, but not for AR glasses, in which the oxygen concentration during growth is kept at 5% by volume or less to suppress light absorption at wavelengths around 420 nm. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 1-96095 Summary of the Invention [Problem to be solved by the invention]

[0008] It was found that the lithium niobate single crystal produced by the production method described in Patent Document 1 absorbs wavelengths in the visible light region, and the reduction in absorption of wavelengths in the visible light region is still insufficient.

[0009] Therefore, an object of the present invention is to provide a lithium niobate single crystal that absorbs little light with wavelengths in the visible light region. [Means for solving the problem]

[0010] As a result of intensive research, the inventors have found that the optical absorption coefficient of lithium niobate single crystal at a wavelength of about 470 nm is affected by platinum impurities in the crystal. The present invention was completed based on this finding.

[0011] The lithium niobate single crystal according to the embodiment of the present invention has a platinum concentration of 1.0 ppm or less in the single crystal.The lithium niobate single crystal preferably has a platinum concentration of 0.5 ppm or less in the single crystal.

[0012] In addition, the lithium niobate single crystal according to the present invention has a difference in the optical absorption coefficient between a wavelength of 470 nm and a wavelength of 600 nm of 0.01 cm. -1 The following is the result.

[0013] In addition, the lithium niobate single crystal according to the present invention has a light absorption coefficient of 0.01 cm at a wavelength of 470 nm. -1 It is preferable that:

[0014] Moreover, the AR glass according to the embodiment of the present invention uses the lithium niobate single crystal according to the above embodiment as a waveguide.

[0015] A method for producing a lithium niobate single crystal according to an embodiment of the present invention is a method for producing a lithium niobate single crystal, comprising: using a crucible made of a platinum-containing material for growing the single crystal; and adjusting the platinum content of the crucible so that the platinum concentration in the grown single crystal is 1.0 ppm or less. Effect of the Invention

[0016] According to the embodiment of the present invention, it is possible to provide a lithium niobate single crystal that has little absorption of light with wavelengths in the visible light region. Also, according to the manufacturing method of the lithium niobate single crystal of the embodiment of the present invention, it is possible to manufacture the lithium niobate single crystal of the embodiment of the present invention. The AR glass of the embodiment of the present invention has little absorption of light with wavelengths in the visible light region in the waveguide. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of an example of a single crystal growth apparatus using the Czochralski method. [Diagram 2] Schematic diagram of reflectance and transmittance measurement by a spectrophotometer to calculate the extinction coefficient. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Specific embodiments of the present invention will be described in detail below. The present invention is not limited to the following embodiments, and can be modified as appropriate without changing the gist of the present invention. In each drawing, a part or whole is depicted diagrammatically as appropriate, and the scale is changed. In order to facilitate understanding of the description, the same components in each drawing are assigned the same reference numerals as much as possible, and duplicated descriptions are omitted. In the following description, the expression "A to B" means "A or more and B or less."

[0019] [Outline of single crystal growth equipment and single crystal growth method] First, we will explain the outline of the single crystal growth device and single crystal growth method for lithium niobate single crystal. Representative methods for growing lithium niobate single crystal include the Cz method (Czochralski method) and the VB method (Vertical Bridgman method).

[0020] In the following, with reference to FIG. 1, a configuration example of a single crystal growth apparatus 10 using the Czochralski method (Cz method) and an overview of a single crystal growth method will be described.

[0021] FIG. 1 is a cross-sectional view showing a schematic configuration of an example of a high-frequency induction heating type single crystal growth apparatus. The example shown in FIG. 1 is a high-frequency induction heating type single crystal growth apparatus, but a resistance heating type single crystal growth apparatus is also used for growing LN single crystals. The difference between the high-frequency induction heating type single crystal growth apparatus and the resistance heating type single crystal growth apparatus is that in the case of the high-frequency induction heating type, an eddy current is generated on the side wall of the metal crucible 12 installed in the work coil 15 by the high-frequency magnetic field formed by the work coil 15, and the crucible 12 itself becomes a heating body by the eddy current, and the temperature environment required for melting the raw material in the crucible 12 and growing the crystal is formed. In the case of the resistance heating type, the heat generated by the resistance heater installed on the outer periphery of the crucible melts the raw material and forms the temperature environment required for growing the crystal. Regardless of which heating method is used, the essence of the Cz method is the same, so below, an example of a single crystal growth method using a high-frequency induction heating type single crystal growth apparatus will be described.

[0022] As shown in FIG. 1, in a high-frequency induction heating type single crystal growth apparatus 10, a crucible 12 is placed in a chamber 11. The crucible 12 has a diameter of, for example, 150 mm to 300 mm and a depth of, for example, 150 mm to 300 mm, and is placed on a crucible stand 13 as shown in FIG. 1. A refractory material 14 is placed in the chamber 11 so as to surround the crucible 12. A work coil 15 is placed so as to surround the crucible 12, and an eddy current flows in the wall of the crucible 12 due to the high-frequency magnetic field formed by the work coil 15, so that the crucible 12 itself becomes a heating element. A pulling shaft (seed rod) 16 is provided at the top of the chamber 11 so as to be rotatable and movable in the vertical direction. A seed holder 17 for holding a seed crystal 1 is attached to the tip of the lower end of the pulling shaft (seed rod) 16.

[0023] In the Cz method, a single crystal piece to become the seed crystal 1 is brought into contact with the molten surface of the single crystal raw material 18 in the crucible 12, and this seed crystal 1 is pulled upward while being rotated by a pulling shaft (seed rod) 16, thereby growing a cylindrical single crystal in the same direction as the crystal orientation of the seed crystal 1.

[0024] In the Cz method, the rotation speed and pulling speed of the seed crystal 1 depend on the type of crystal to be grown and the temperature environment during growth, and must be appropriately selected according to these conditions. In addition, when growing a crystal, the solidification latent heat generated by the crystallization of the melt at the growth interface must be released upward through the seed crystal, so the growth must be performed under a temperature gradient in which the temperature decreases from the growth interface upward. In addition, in order to prevent the shape of the grown crystal from bending or twisting, the growth must be performed under a temperature gradient in which the temperature increases horizontally from the growth interface to the crucible wall and vertically from the growth interface to the crucible bottom.

[0025] When growing an LN single crystal, a crucible 12 made of platinum (Pt), which has a melting point of about 1760°C and is chemically stable, is used because the melting point of the LN crystal is 1250°C. The pulling speed during growth is generally about several mm / hour, and the rotation speed is about several to several tens of rpm (for example, 3 rpm to 10 rpm). In addition, the inside of the furnace during growth is generally an atmosphere of air or a mixed gas of nitrogen and oxygen with an oxygen concentration of about 20%. After the crystal is grown to a desired size under these conditions, the grown crystal is separated from the melt by changing the pulling speed or gradually increasing the melt temperature, and then the power of the growth furnace is reduced at a predetermined rate to slowly cool it, and the crystal is taken out of the growth furnace after the temperature inside the furnace becomes close to room temperature.

[0026] Crystals grown in this way are removed from the furnace and then subjected to an annealing process to remove residual distortion caused by temperature differences within the crystal, and a poling process to align the direction of the spontaneous polarization within the crystal. The crystals are then handed over to the substrate processing step, where they are sliced, polished, etc.

[0027] The above-described method for producing LN single crystals is a method for producing LN single crystals used as a material for surface acoustic wave elements (SAW filters). When the LN single crystal produced by this method is used as a material for the waveguide of AR glasses, it has been found that the LN single crystal produced above has a light absorption peak at a specific wavelength in the visible light range, and when an image passes through the waveguide by total reflection, the attenuation of light at a specific wavelength becomes large, resulting in a problem that the color of the image displayed on the AR glasses differs from the intended image. When the LN single crystal is used as a material for the waveguide of AR glasses, it is particularly important to reduce the difference between the light absorption coefficient at a wavelength of 470 nm in the visible light range and the light absorption coefficient at a wavelength of 600 nm.

[0028] The inventors conducted research to solve the above problems, and as a result of investigating the difference between the optical absorption coefficient of LN single crystal at wavelengths of 470 nm and 600 nm and the influence of impurities in the crystal, they found that there is a correlation with platinum (Pt). The inventors also found that the optical absorption coefficient of LN single crystal at wavelengths of around 470 nm is influenced by platinum (Pt) impurities in the crystal. The LN single crystal and the manufacturing method thereof according to this embodiment were completed through further research based on these findings.

[0029] The LN single crystal according to this embodiment will be described. The LN single crystal according to one aspect of this embodiment is characterized in that the concentration (content) of platinum (Pt) in the single crystal is 1.0 ppm or less. In addition, the LN single crystal according to one aspect of this embodiment has a difference in the optical absorption coefficient between a wavelength of 470 nm and a wavelength of 600 nm of 0.01 cm. -1 The LN single crystal according to one aspect of this embodiment is characterized in that it has a light absorption coefficient of 0.01 cm -1 The present invention is characterized in that:

[0030] As shown in Table 1, which will be described later, the LN single crystal according to this embodiment can significantly reduce the difference between the optical absorption coefficient at wavelengths of 470 nm and 600 nm by suppressing the platinum (Pt) concentration, and can significantly reduce the optical absorption coefficient at a wavelength of 470 nm.

[0031] In the LN single crystal of this embodiment, the upper limit of the platinum (Pt) concentration is preferably 1.0 ppm or less, and more preferably 0.5 ppm or less. In the LN single crystal, the difference between the light absorption coefficient at a wavelength of 470 nm and the light absorption coefficient at a wavelength of 600 nm is 0.01 cm -1 Less than 0.005cm is preferable. -1 By setting the platinum (Pt) concentration in the LN single crystal to 1.0 ppm or less, the difference between the optical absorption coefficient at wavelengths of 470 nm and 600 nm (sometimes referred to as the difference between the optical absorption coefficients at wavelengths of 470 nm and 600 nm) can be reduced to, for example, 0.01 cm -1It is preferable that the platinum (Pt) concentration of the LN single crystal is 0.5 ppm or less, which can reduce the difference in the optical absorption coefficient between wavelengths of 470 nm and 600 nm, for example, to 0.005 cm -1 In the LN single crystal, the lower limit of the platinum (Pt) concentration is 0 ppm or more, and may be 0.1 ppm or more. In the LN single crystal, the lower limit of the difference between the optical absorption coefficient at a wavelength of 470 nm and the optical absorption coefficient at a wavelength of 600 nm is not particularly limited, but may be 0 cm -1 More than 0.001cm -1 or more. In the LN single crystal, when the platinum (Pt) concentration exceeds 1.0 ppm, the difference between the optical absorption coefficient at a wavelength of 470 nm and the optical absorption coefficient at a wavelength of 600 nm becomes large. In the LN single crystal, when the platinum (Pt) concentration exceeds 1.0 ppm, the optical absorption coefficient at a wavelength of 470 nm becomes large, and the difference between the optical absorption coefficient at a wavelength of 470 nm and the optical absorption coefficient at a wavelength of 600 nm becomes large.

[0032] In addition, in the case of an LN single crystal, if a transition metal other than platinum is present as an impurity in the crystal, it will affect the difference in the optical absorption coefficient at wavelengths of 470 nm and 600 nm in the visible light region, so as in Examples 1 and 2 and Comparative Example 1, the concentration (content) of elements other than platinum was also analyzed by ICP mass spectrometry (ICP-MS), but in this example, no elements were found that showed a correlation with the difference in the optical absorption coefficient at wavelengths of 470 nm and 600 nm. Table 2, which will be described later, shows the analysis results for representative transition metal elements.

[0033] The concentration of impurities other than platinum in the LN single crystal will now be described. The upper limit of the Fe concentration in the LN single crystal is preferably 2 ppm or less, more preferably 1.5 ppm or less. The lower limit of the Fe concentration is 0 ppm or more, and may be 0.5 ppm or more, or 1.0 ppm or more. When the Fe concentration is within the above range, it does not have a significant effect on the optical absorption coefficient at wavelengths of 470 nm and 600 nm in the visible light region.

[0034] The upper limit of the Ni concentration in the LN single crystal is preferably 0.2 ppm or less, more preferably 0.1 ppm or less. The lower limit of the Ni concentration is 0 ppm or more, and may be 0.05 ppm or more. When the Ni concentration is within the above range, it does not significantly affect the optical absorption coefficient at wavelengths of 470 nm and 600 nm in the visible light region.

[0035] The upper limit of the Cr concentration in the LN single crystal is preferably 0.4 ppm or less, more preferably 0.3 ppm or less. The lower limit of the Cr concentration is 0 ppm or more, and may be 0.1 ppm or more. When the Cr concentration is within the above range, it does not significantly affect the optical absorption coefficient at wavelengths of 470 nm and 600 nm in the visible light region.

[0036] The upper limit of the Cu concentration in the LN single crystal is preferably 0.2 ppm or less, more preferably 0.1 ppm or less. The lower limit of the Cu concentration is 0 ppm or more, and may be 0.05 ppm or more. When the Cu concentration is within the above range, it does not significantly affect the light absorption coefficient at wavelengths of 470 nm and 600 nm in the visible light region. Note that the LN single crystal may contain elements other than those mentioned above within the scope of the present invention.

[0037] It is also important to suppress the peak of the optical absorption coefficient at a wavelength of 470 nm in the LN single crystal. The optical absorption coefficient of the LN single crystal at a wavelength of 470 nm is 0.01 cm -1 or less, preferably 0.005 cm -1 For example, by reducing the platinum (Pt) concentration in the single crystal, the optical absorption coefficient at a wavelength of 470 nm can be reduced to 0.01 cm -1 For example, by making the platinum (Pt) concentration in the single crystal 1.0 ppm or less, the optical absorption coefficient at a wavelength of 470 nm can be reduced to 0.01 cm -1 The light absorption coefficient at a wavelength of 470 nm can be reduced to 0.005 cm by setting the platinum (Pt) concentration to 0.5 ppm or less. -1In the case of an LN single crystal, the lower limit of the optical absorption coefficient at a wavelength of 470 nm is not particularly limited, but is preferably 0 cm -1 More than 0.001cm -1 More than that is fine.

[0038] In this specification, the concentration (content) of elements such as platinum (Pt) in the LN single crystal is determined by ICP mass spectrometry (Inductively Coupled Plasma Mass Spectrometry: ICP-MS). ICP mass spectrometry can be performed by the method described in the Examples. In this specification, the optical absorption coefficient is a value determined by the method described in the Examples.

[0039] The LN single crystal may be in the form of an ingot, a wafer, or a thin plate. The size of the LN single crystal is not particularly limited, but may be, for example, 1 inch or more, 6 inches, or 8 inches in diameter. The thickness of the crystal is not particularly limited, but may be 100 μm or more, for example, 100 μm or more and 1000 μm or less. For example, in the case of a wafer, the thickness may be 250 μm or more and 1000 μm or less, and a thickness of 350 μm to 500 μm is often used. In the case of an ingot, the thickness may be 10 mm to 150 mm.

[0040] As described above, the LN single crystal according to one aspect of this embodiment is characterized in that the platinum (Pt) concentration (content) in the single crystal is 1.0 ppm or less. In addition, the LN single crystal according to one aspect of this embodiment has a difference in the optical absorption coefficient between a wavelength of 470 nm and a wavelength of 600 nm of 0.01 cm. -1 The LN single crystal according to one aspect of this embodiment is characterized in that it has a light absorption coefficient of 0.01 cm -1 The LN single crystal according to the aspect of this embodiment has the following characteristics: All of the LN single crystals have low absorption of light with wavelengths in the visible light region.

[0041] Since the LN single crystal according to this embodiment has the above-mentioned characteristics, it can be suitably used for the waveguide of an AR display device (an augmented reality display device) such as AR glasses (augmented reality glasses). For example, the AR display device and the AR glasses may be configured to use the LN single crystal according to this embodiment as a waveguide. For example, such an AR display device and AR glasses may use the LN single crystal according to this embodiment for at least a part of the waveguide, and may have any other configuration.

[0042] Next, a method for producing the LN single crystal according to the present embodiment will be described. The LN single crystal according to the present embodiment can be produced by, for example, reducing the concentration (content) of platinum (Pt) in the crystal.

[0043] There are several methods for reducing the platinum impurity concentration in lithium niobate single crystals. For example, a crucible used for crystal growth can be made of a platinum-iridium alloy, and the platinum ratio can be reduced to obtain lithium niobate single crystals with a low platinum impurity concentration.

[0044] Next, we will explain how to reduce the platinum impurity concentration in lithium niobate single crystals. First of all, platinum impurities in LN single crystals may be impurities contained in the raw materials. It is also important to improve the purity of the raw materials. It is preferable to use raw materials with a purity of 99.99 or higher. However, since platinum is not usually used in the raw material manufacturing stage for LN single crystals, the possibility is thought to be small.

[0045] Next, the material of the crucible used during growth is also important. Methods for growing lithium niobate single crystals include the Cz method (Czochralski method) and the VB method (vertical Bridgman method) mentioned above. The crucible used to melt the raw material is used. In the Cz method, crucibles made of materials with high melting points and chemical stability are generally used. For example, platinum, iridium, or alloys of these. In growing LN single crystals, platinum crucibles, which are relatively inexpensive, are usually used. Platinum crucibles are chemically stable and do not easily dissolve in solutions, but as shown in Table 1, which will be explained later, a small amount of platinum dissolves in the melt (raw material melt), and platinum (Pt) from the crucible is taken into the crystal during growth, affecting the optical absorption coefficient.

[0046] Therefore, in this embodiment, a crucible made of platinum or platinum-iridium alloy was used for the test, and it was found that the lower the platinum content of the platinum-iridium alloy, the less the elution into the LN single crystal. Therefore, the method for producing an LN single crystal according to this embodiment may be a method for producing an LN single crystal, in which the material of the crucible used for growing the single crystal is a crucible containing platinum, and the platinum content of the crucible may be adjusted so that the platinum concentration in the grown single crystal is 1.0 ppm or less. This can be carried out, for example, by the method described in the examples. For example, when adjusting the platinum content of the crucible so that the platinum concentration in the single crystal is 1.0 ppm or less, for example, the platinum content of the platinum-iridium alloy crucible is 50% or less, preferably 20% or less. The dissolution of iridium into the LN single crystal did not affect the optical absorption coefficient of the LN single crystal in the visible light region.

[0047] The oxygen concentration in the furnace during growth is generally either the atmosphere or a nitrogen-oxygen mixed gas atmosphere with an oxygen concentration of about 20%. However, when iridium is contained in a platinum-iridium alloy or the like, it is preferable to set the oxygen concentration low because iridium is easily combined with oxygen and sublimes, and it is preferable that the oxygen concentration in the furnace during growth be more than 5% and be either the atmosphere or about 20% in terms of oxygen concentration, taking into account the stability of the crystal.

[0048] In this embodiment, the platinum impurity concentration in the lithium niobate single crystal is reduced by reducing the platinum concentration in the alloy in the crucible, but the present invention is not limited to this example. For example, a method for producing a crystal that does not use platinum, such as the cold crucible method, may be used.

[0049] As described above, the method for producing an LN single crystal according to this embodiment is a method for producing an LN single crystal, and includes adjusting the platinum content of the crucible used for growing the single crystal so that the platinum concentration in the grown single crystal is 1.0 ppm or less, and the crucible is made of a platinum-containing material. In addition, in the method for producing an LN single crystal according to this embodiment, other configurations than those described above can be appropriately used, for example, known methods. According to the method for producing a lithium niobate single crystal according to this embodiment, the lithium niobate single crystal according to this embodiment can be produced. EXAMPLES

[0050] The present invention will be specifically described below using examples, but the present invention is not limited to these examples in any way.

[0051] [Example 1] Using the high-frequency induction heating type single crystal growth apparatus shown in Figure 1, the flow rates of nitrogen gas and oxygen gas were adjusted so that the oxygen concentration in the growth furnace was 20%, and Z-axis pulled LN crystals were grown by the Cz method. Note that Z-axis pulling refers to the crystal growth orientation (crystal orientation of the seed crystal).

[0052] In order to reduce the platinum concentration in the LN crystal to be produced, LN powder with a purity of 99.99 or more was charged as raw material 18 into crucible 12 containing a platinum-iridium alloy with a platinum ratio of 20%, and after melting raw material 18, the tip of seed crystal 1 was immersed in the raw material molten liquid in crucible 12 and pulled up while rotating to grow an LN single crystal ingot with a diameter of 6 inches (=152 mm) and a straight body length of 70 mm. The grown LN single crystal ingot was separated from the raw material molten liquid, and the crystal was cooled to near room temperature and then removed.

[0053] The single crystal ingot was annealed and poled, and then the outer periphery was ground into a cylindrical shape and cut into wafers with a thickness of 500 μm using a multi-wire saw. One wafer each was sampled from the upper and lower sides of the cut crystal, crushed with an agate ball mill, sieved with a 150 μm mesh, mixed with a reagent mixture of hydrofluoric acid and nitric acid, and then dissolved using a microwave pretreatment device. The platinum concentration of the dissolved sample was analyzed by ICP-MS, and was 0.3 ppm in each wafer. To measure the absorption coefficient, both sides of the remaining wafers were chemically mechanically polished with colloidal silica. The absorption coefficient of the polished wafer was measured using a spectrophotometer (Agilent, Cary 7000). In this example, the analytical accuracy of the elements by ICP-MS was 0.1 ppm.

[0054] In determining the absorption coefficient, first, the incident angle θ of light on the sample was fixed at 6°, and the reflectance R and transmittance T were measured. The detector angle when measuring the reflectance R was 2θ = 12°, and when measuring the transmittance, the detector angle was 180°. In addition, to reduce noise in the measured values, the incident light was passed through a depolarizing plate. Based on the principle that the sum of the reflectance R, transmittance T, and absorptance A is 100%, the absorptance A was calculated from the measured reflectance R and transmittance T using the following formula (1). Figure 2 shows a schematic diagram of the measurement of reflectance and transmittance using a spectrophotometer to calculate the absorption coefficient.

[0055]

number

[0056] The absorption coefficient is defined as the following equation (2) according to the Beer-Lambert law, using α in the natural logarithm form and β in the common logarithm form. In this specification, however, the absorption coefficient uses β in the common logarithm form.

number

[0057]

number

[0058] From equations (1) and (3), the absorption coefficient β is given by the following equation (4).

number

[0059] In this specification, the absorption coefficient β (cm −1 ) was calculated by measuring the reflectance R and transmittance T of a sample with a thickness x (cm) using equation (4).

[0060] The absorption coefficient can also be calculated using the following formula (5), which takes multiple reflections within the sample into account, but it should be noted that this will result in a slight difference from the value calculated using formula (4). All of the absorption coefficients in this embodiment are calculated using the definition of formula (4).

[0061]

number

[0062] In Example 1, the absorption coefficient calculated by the above-mentioned formula (4) was as follows: (1) 0.0039 cm at a wavelength of 470 nm -1 (2) 0.0006 cm at a wavelength of 600 nm -1 , (1)-(2) is 0.0033 cm -1 It was.

[0063] [Example 2] Next, the material of the crucible was changed to a platinum-iridium alloy with a platinum ratio of 50%, and the crystal was grown under the same conditions as in Example 1, and the platinum concentration and absorption coefficient were measured. As a result, the platinum concentration was 0.8 ppm. The absorption coefficient was (1) 0.0079 cm at a wavelength of 470 nm. -1 (2) 0.0004 cm at a wavelength of 600 nm -1 , (1)-(2) is 0.0075 cm -1 It was.

[0064] [Comparative Example 1] Next, the material of the crucible was changed to pure platinum, and the crystal was grown under the same conditions as in Example 1, and the platinum concentration and absorption coefficient were measured. As a result, the platinum concentration was 1.2 ppm. The absorption coefficient was (1) 0.0110 cm at a wavelength of 470 nm. -1 (2) 0.0007 cm at a wavelength of 600 nm -1 , (1)-(2) is 0.0103 cm -1 It was.

[0065] The results of Examples 1 and 2 and Comparative Example 1 are summarized in Table 1.

[0066] [Table 1]

[0067] In addition, when transition metals other than platinum are present as impurities in the LN crystal, they may generate an absorption peak near 470 nm, so elements other than platinum in Examples 1 and 2 and Comparative Examples 1 and 2 were also analyzed by ICP-MS, but no elements were found that showed a correlation with the absorption coefficient at 470 nm. Table 2 shows the analysis results of representative transition metal elements by ICP-MS.

[0068] [Table 2]

[0069] These results show that the absorption peak near 470 nm can be suppressed by reducing the platinum impurity concentration during crystal growth. In addition, by keeping the platinum impurity concentration during crystal growth below 0.1 ppm, the difference in the optical absorption coefficient between the wavelengths of 470 nm and 600 nm is reduced to 0.01 cm. -1 It has been confirmed that the following can be achieved: It has been confirmed that the LN single crystal according to this embodiment has the characteristic of having little absorption of light with wavelengths in the visible light region.

[0070] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. For example, the single crystal of this embodiment may be combined with the items described in the manufacturing method and examples of this embodiment, and the manufacturing method of this embodiment may be combined with the items described in the single crystal and examples of this embodiment. In addition, to the extent permitted by law, the disclosures of all documents cited in the above-mentioned embodiments are incorporated by reference and made part of the description in this text.

Claims

1. The platinum concentration in the single crystal is 0.8 ppm or less, and The difference between the light absorption coefficient at a wavelength of 470 nm and the light absorption coefficient at a wavelength of 600 nm is 0.01 cm −1 or less. Lithium niobate single crystal.

2. 2. The lithium niobate single crystal according to claim 1, wherein the concentration of platinum in the single crystal is 0.5 ppm or less.

3. The light absorption coefficient of 470 nm is 0.01 cm -1 2. The lithium niobate single crystal according to claim 1, wherein:

4. 4. An AR glass using the lithium niobate single crystal according to claim 1 as a waveguide.

5. A method for producing a lithium niobate single crystal, comprising the steps of: The material of the crucible used for growing the single crystal is a crucible containing platinum, and adjusting the platinum content in the crucible so that the platinum concentration in the grown single crystal is 1.0 ppm or less.

Citation Information

Patent Citations

  • Production of lithium niobate single crystal

    JP1989096095A

  • Production of lithium niobate single crystal and optical element therefrom

    JP1993097591A

  • METHOD FOR GROWING LiNbO3 SINGLE CRYSTAL

    JP2018100202A